2005
DOI: 10.1081/ese-200048264
|View full text |Cite
|
Sign up to set email alerts
|

Indicator Organisms Associated with Stormwater Suspended Particles and Estuarine Sediment

Abstract: This study examined the fate of indicator organisms (fecal coliform, E. coli, and enterococci) from urban stormwater runoff associated with estuarine sediments and stormwater suspended particles. The research found a significant increase of fecal coliform, E. coli, and enterococci in the estuarine sediments at study sites following a given stormwater event. The sedimentation mechanism was linked to an increase in indicator organisms in the estuarine sediments. These indicator organisms attached to stormwater s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 19 publications
5
82
0
Order By: Relevance
“…and that much higher concentrations can be present in bottom sediments (Davies et al 1995;Jeng et al 2005). While somewhat speculative, it is possible that this increased persistence could lead to higher levels of particle-associated enterococci becoming resuspended from underlying pond sediment during high flows.…”
Section: Wet Pond Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…and that much higher concentrations can be present in bottom sediments (Davies et al 1995;Jeng et al 2005). While somewhat speculative, it is possible that this increased persistence could lead to higher levels of particle-associated enterococci becoming resuspended from underlying pond sediment during high flows.…”
Section: Wet Pond Efficiencymentioning
confidence: 99%
“…Quantifying the relative fractions of organisms associated with particles is essential to modeling efforts as particlemicrobe aggregates settle more quickly from the water column and thus travel shorter distances in receiving waters (Gannon et al 1983;Jeng et al 2005). Previous work also links microbial association with sediments to prolonged survival (Gerba & Schaiberger 1975;Gerba & McLeod 1976;Howell et al 1996;Jamieson et al 2004b) and/or regrowth (Hendricks & Morrison 1967;LaLiberte & Grimes 1982;Desmarais et al 2002;Lee et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed a 10-fold decrease of FC concentrations in runoff water after the silt fraction had settled as compared to the settling sand fraction, which suggested much greater attachment to the silt fraction. Jeng et al (24) studied E. coli attachment to five sediment fractions in fresh storm water. They found that approximately 80%, 18%, and 2% of attached E. coli cells were associated with the silt fraction, the clay fraction, and the sand fraction, respectively.…”
mentioning
confidence: 99%
“…Studies have shown that within sediment there are higher populations of TCs than the overlaying water (Smith et al, 2008) as sediments serve as a hospitable environment for bacterial survival due to the availability of organic matter (Jamieson et al, 2005) suggesting that E. coli may be being deposited into the stream and incorporated within the sediment. Subsequently during storm events bacteria can be re-suspended into the water column and continue to flow downstream (Jeng et al, 2005), posing a potential threat to bathing waters on the sandy beach at Aberffraw at the mouth of the river Ffraw since mean E. coli colonies within both streams exceed 2,000 colonies per 100 ml which would fail to meet the required standards for the EU bathing water directive (2006).…”
Section: Streamsmentioning
confidence: 99%